WORK, INCOME SUPPORT, AND CRIME IN THE DUTCH WELFARE STATE: A LONGITUDINAL STUDY FOLLOWING VULNERABLE YOUTH INTO ADULTHOOD1. Issue 4 (8th October 2015) - VERBRUGGEN, JANNA; APEL, ROBERT; VAN DER GEEST, VICTOR R.; BLOKLAND, ARJAN A. J.
Abstract : Life‐course criminological research has consistently suggested that employment can reduce criminal behavior. However, it is unclear whether the financial aspects of employment or the social control that inheres in employment best explains the relationship between employment and reduced offending. By using longitudinal information on a sample of men and women (N = 540) who were institutionalized in a Dutch juvenile justice institution in the 1990s, this study examines the effects of employment as well as the different types of income support on crime. Random‐ and fixed‐effects models show that for men, both work and income support are associated with a reduction in the rate of offending. For women, however, although employment is correlated with a lower offending rate, receiving income support, and in particular disability benefits, is correlated with a higher offending rate. The findings support both theories that stress the financial motivation for crime as well as theories that emphasize the importance of informal social control for reducing offending.